العوامل المؤثرة في الاصابة بداء السكري لكافة الفئات العمرية وتحليلها احصائيا في مدينة درنة (Al-Farooq Journal of Sciences, 2026)
The study aimed to identify the factors associated with diabetes among residents of the city of Derna, as well as to evaluate the social and economic impacts that the disease has on patients and their families. To evaluate the relationship between genetic and previous medical factors and the risk of developing diabetes, the methodology was based on the SPSS program through the Pearson correlation coefficient, simple linear regression analysis, and inferential tests: it included the (T) test and the (F) test, as the results of the study showed that the genetic factor is considered the most influential determinant of diabetes in the city of Derna, ahead of the rest of the factors in the total sample and in both sexes, with clear spatial variations indicating the concentration of genetic predisposition in some localities. The results also revealed the pivotal role of overweight and unhealthy dietary patterns as influential behavioral factors, reflecting shifts in lifestyles and lack of physical activity. The age factor came in last place in terms of relative influence, which confirms that diabetes is no longer linked to chronological age as much as it is linked to genetic, psychological and behavioral factors. Statistical analyzes showed the presence of very strong and statistically significant direct correlations between all independent variables and the dependent variable, with high values of correlation and determination coefficients. It turns out that physiological and psychological variables, especially weight gain, endocrine disorders, and psychological emotions, have the highest explanatory power for the variation in disease incidence. Statistical significance tests also confirmed the rejection of the null hypothesis and the strength of the model used, which supports the reliability of the results and their validity in building future explanatory and predictive models.
Keywords: Diabetes, Derna city, medical geography.